A Multi-Disciplinary Approach to Assess the Welfare Impacts of a New Virtual Fencing Technology - Lee, Caroline; Campbell, Dana L. M. (Frontiers in Veterinary Science, 2021)
Virtual fencing involving the application of audio cues and electrical stimuli is being commercially developed for cattle. Virtual fencing has the potential to improve productivity through optimised pasture management and utilisation by grazing animals. The application of virtual fencing initiates public concern for the potential welfare impacts on animals due to the aversive nature of using an electrical stimulus. It is therefore important to provide welfare assurance of the impacts of virtual fencing on livestock. In this paper, we provide an overview of the welfare assessment and validation stages for virtual fencing which could be applied to other new technologies utilising novel systems. An understanding of stress measures and their suitability for use in specific contexts is discussed, including the use of glucocorticoids to measure both acute and chronic stress, and behavioural responses and patterns to indicate welfare states. The importance of individual differences in relation to learning and cognition are also highlighted. Together, this multi-disciplinary approach to welfare assessment provides a tool kit that may be applied for welfare assurance of some new technologies and systems for farm animals.